Kombinasi Metode Pembobotan Rank Reciprocal dan Simple Additive Weighting Dalam Pemilihan Tempat Servis Kendaraan - Nuroji Nuroji (CHAIN: Journal of Computer Technology, Computer Engineering, and Informatics, 2024)
The choice of vehicle service place is an important decision for vehicle owners because it will affect the quality of maintenance and service received by their vehicle. Some of the problems that may arise in the selection of vehicle service places include uncertainty in service quality, unaffordable prices, lack of availability of spare parts, and communication problems between customers and mechanics. The combination of reciprocal rank weighting (RR) and simple additive weighting (SAW) methods in vehicle service site selection can improve accuracy and objectivity in decision making. The RR method is used to derive the relative ranking of each alternative based on the decision maker's preference for certain criteria, while the SAW method is used to weigh and combine the weights of criteria in a structured manner. The ranking results gave a rank 1 result with a value of 0.9256 obtained by TR Service Place, rank 2 with a value of 0.8291 obtained by the AS Service Place, and rank 3 with a value of 0.7884 obtained by DW Service Place.